Research on calculation formula of cable force test under the influence of shock absorber - Chen Quan; Xu Shangchuan; Zhou Xueming (E3S Web of Conferences)
Based on the theory of structural vibration and the calculation formula of cable force considering the bending stiffness of cable, the practical calculation formula of cable force considering the influence of shock absorber is derived by using the law of conservation of energy. When the above factors affecting the cable force are not considered, the formula is the classical string vibration formula. By comparing the traditional cable force formula with the modified formula containing shock absorber, the calculation formula of the effective length of the cable is derived. The calculation formula of effective length has taken the influence of shock absorber into account. The cable force value can be calculated by taking the effective length of derrick into the classical mechanics formula. The accuracy of the practical formula for calculating the cable force and the effective length of the articulated cable considering the influence of shock absorber is verified by the frequency measurement results of the real bridge. Compared with the traditional cable force formula, the calculation accuracy of the cable force formula presented in this paper is higher.